Societal's Attitude Towards the Essential of English for the Tourism Sector: Expectations and Actions - Pratiwi, Widya Rizky; Juhana, Juhana; Gusti Acfira, Lukytta (Institut Agama Islam Negeri (IAIN) Curup, 2023)
English is essential for national development involving the tourism sector. Unfortunately, it just serves as a foreign language in Indonesia, resulting in low speaking performance. This study observed stakeholders' and community's efforts to boost English-speaking fluency in the tourism object zone. It was a qualitative case study through interviews, document analysis, and photos in collecting the data. The research was done in Tana Toraja and Bulukumba regency of South Sulawesi province by involving stakeholders. The findings show that Stakeholders and local society are regularly active in training on the use of English for Specific Purposes (ESP), such as English for tour guides, hotel services, selling handicrafts, etc. Stakeholders also introduce and train the use of various kinds of Artificial Intelligence to improve English skills, such as